2014
DOI: 10.1021/jf5000776
|View full text |Cite
|
Sign up to set email alerts
|

Anticarcinogenic Effects of Products of Heat-Processed Ginsenoside Re, a Major Constituent of Ginseng Berry, on Human Gastric Cancer Cells

Abstract: Ginsenoside Re is a triol type triterpene glycoside and is abundantly present in ginseng berry. In the present study, we verified that ginsenoside Re can be transformed into less-polar ginsenosides, namely, Rg2, Rg6, and F4, by heat-processing. The products of heat-processed ginsenoside Re inhibited phosphorylation of CDK2 at Thr160 by upregulation of p21 level, resulting in S phase arrest. The products of heat-processed ginsenoside Re also activated caspase-8, caspase-9, and caspase-3, followed by cleavage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 22 publications
1
42
0
Order By: Relevance
“…Rare ginsenosides such as Rk 3 , Rh 4 , Rg 5 , Rg 6 , F 4 , Rg 3 , Rh 2 and so on, which can degrade from the major ones by thermal and acid or alkali treatments, have been confirmed to have extremely high cancer inhibition effect. [40][41][42][43] Therefore, inspired from the thermal degradation of ginsenoside Re leading to the formation of Re-derived anticancer compositions, we selected Re as carbon source to obtain CDs functioning both as imaging reagents and effective anticancer drugs through the hydrothermal process. During the hydrothermal synthesis of ginsenoside Re-based CDs (Re-CDs), the original materials would be probably destructed and reconstructed to form more novel constituents and active functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Rare ginsenosides such as Rk 3 , Rh 4 , Rg 5 , Rg 6 , F 4 , Rg 3 , Rh 2 and so on, which can degrade from the major ones by thermal and acid or alkali treatments, have been confirmed to have extremely high cancer inhibition effect. [40][41][42][43] Therefore, inspired from the thermal degradation of ginsenoside Re leading to the formation of Re-derived anticancer compositions, we selected Re as carbon source to obtain CDs functioning both as imaging reagents and effective anticancer drugs through the hydrothermal process. During the hydrothermal synthesis of ginsenoside Re-based CDs (Re-CDs), the original materials would be probably destructed and reconstructed to form more novel constituents and active functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-cancer activity: Recent studies have reported that the ginseng berry exhibits anti-cancer activity in in vitro [20][21][22][23][24][25] and in vivo [26,27], as well as the ability to attenuate chemotherapy-induced side effects [28,29]; these effects result from the promotion of dendritic cell maturation. Interestingly, the ginseng berry induced a higher degree of co-stimulatory molecule up regulation than the root extract at the same concentrations [30].…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…Recent studies have reported that the ginseng berry also exhibits anti-cancer activity in in vitro [2,[73][74][75][76][77] side effects [80,81]; these effects result from the promotion of dendrite cell maturation. Interestingly, the ginseng berry induced a higher degree of co-stimulatory molecule up regulation than the root extract at the same concentrations [82].…”
Section: Anti-cancer Activitymentioning
confidence: 99%